The Current State of Molecular Testing in the BRAF-Mutated Melanoma Landscape - Vanni, Irene; Tanda, Enrica Teresa; Spagnolo, Francesco; Andreotti, Virginia; Bruno, William; Ghiorzo, Paola (Frontiers in Molecular Biosciences, 2020)
The incidence of Melanoma, one among the most lethal cancers, is widespread increasing.” Metastatic melanoma has a poor prognosis representing about 90% of skin cancer mortality. The increased knowledge of tumour biology and the greater understanding of the immune system role in anti-tumour response, allowed to develop a more rational approach to systemic therapies. “The discovery of activating BRAF mutations in half of all melanomas has led to the development of molecularly targeted therapy with BRAF and MEK inhibitors which dramatically improved outcomes of patients with stage IV BRAF-mutant melanoma. More recently, the results of clinical phase III studies conducted in the adjuvant setting led to the combined administration of BRAF and MEK inhibitors also in patients with resected high-risk melanoma (stage III). Therefore, BRAF mutation testing has become a priority to determine the oncologist’s choice and course of therapy. In this review, we will report the molecular biology-based strategies used for BRAF mutation detection with the main advantages and disadvantages of the most commonly used diagnostic strategies. The timing of such molecular assessment in patients with cutaneous melanoma will be discussed, as well as considerations and approaches for accurate and effective BRAF testing.